Comparative Study between Classical and Fuzzy Filters for Removing Different Types of Noise from Digital Images - Z. Ahmood, Tarik . (Iraqi Journal of Science, 2023)
The aim of this paper is to compare between classical and fuzzy filters for removing different types of noise in gray scale images. The processing used consists of three steps. First, different types of noise are added to the original image to produce a noisy image (with different noise ratios). Second, classical and fuzzy filters are used to filter the noisy image. Finally, comparing between resulting images depending on a quantitative measure called Peak Signal-to-Noise Ratio (PSNR) to determine the best filter in each case.The image used in this paper is a 512 * 512 pixel and the size of all filters is a square window of size 3*3. Results indicate that fuzzy filters achieve varying successes in noise reduction in image compared to classical filters. Mathlab 2012b program is used to add noise to the original image and remove it because it has powerful tools to deal with digital images.